Outlet Glacier and Landscape Evolution of Victoria Land, Antarctica - Ross Whitmore (8512161) (2020)
Terrestrial cosmogenic exposure studies are an established and rapidly evolving tool for landscapes in both polar and non-polar regions. This thesis takes a multifaceted approach to utilizing and enhancing terrestrial cosmogenic methods. The three main components of this work address method development, reconstructing surface-elevation-changes in two large Antarctic outlet glaciers, and evaluating bedrock erosion rates in Victoria Land, Antarctica. Each facet of this work is intended to enhance its respective field, as well as benefit the other sections of this thesis. Quartz purification is a necessary and critical step to producing robust and reproducible results in terrestrial cosmogenic nuclide studies. Previous quartz purification work has centred on relatively coarse sample material (1 mm-500 μm) and is effective down to 125 μm. However, sample material finer than that poses significant purification challenges and this material is usually discarded. The new purification procedure outlined in this thesis shows that very fine sand size material (125-63 μm) can be reliably cleaned for use in terrestrial cosmogenic nuclide studies. The results below show that 35% mass loss in very fine-grained quartz is sufficient to remove major elements (Al, Ti, Na, K, Fe, Mg, Ca, Mn,) and trace elements (9Be, and 10B) along with meteoric 10Be. Insufficient leaching is most detrimental to Al concentration, however errors up to 27% in exposure age and up to 29% in erosion rate are possible if meteoric 10Be is not fully removed from quartz during the HF leaching stages. Outlet glaciers have been well observed since the beginning of the satellite era, approximately 60 years ago. However, we do not currently know how these important glaciers, which drain a significant portion of the Antarctic Ice Sheet, have behaved on centennial to millennial timescales. Dating glacial erratics deposited by a thinning outlet glacier provides a window into the long-term outlet glacier and ice sheet response to climatic forcing. New results in this thesis constrain the thinning history of Mawson and Tucker glaciers over the last several thousand years. Mawson Glacier undergoes rapid thinning from at least ~6.5 kya to ~4.9 kya then transitions to slower thinning until ~1 kya, with a minimum of 250 m of ice-surface-lowering. While Tucker Glacier ~450 km north undergoes gradual thinning from ~19 kya to ~5 kya with ~300 m of ice-surface-lowering. The results of this work show that either the Tucker Glacier was not significantly affected by the Ross Ice Shelf grounding line, or that Antarctic mountain glaciers respond differently to the outlet glaciers connected to the Easty Antarctic Ice Sheet. The style, rate, magnitude, and duration of thinning is unique to each outlet glacier, even with similar climate forcing. The results of this work shed light on the style and duration of outlet glacier thinning and retreat that is possible following a climate perturbation. Antarctica’s average bedrock erosion rate is consistently lower than 4.5 m/Myr, the lowest bedrock erosion rates for any region on Earth. Therefore, many cosmogenic dating studies assume zero erosion when calculating exposure ages. However, previous erosion rate work in Antarctica is biased to arid high-elevation inland sites (~60% of work) and the hyperarid ice-free McMurdo Dry Valleys (~40% of work). These studies do not capture the effects of coastal maritime climates, where many outlet glacier studies are conducted, on the rate of bedrock erosion. New results presented in this thesis show that the Northern Victoria Land coast has the highest known erosion rate in Antarctica. Two sample sites were selected, one coastal and one in the interior. The coastal bedrock erosion rates are 8.86±0.78 m/Myr and 7.15±0.6 m/Myr while the interior bedrock erosion rates are 1.07±0.08 m/Myr and 0.42±0.03 m/Myr. The coastal erosion rates are average for non-polar cold climates while the inland sites are below average for polar erosion rates. The results suggest a strong gradient in the rate of erosion is present from the Antarctic coastline inland. If exposure ages are not calculated with an appropriate erosion rate the apparent age may under-estimate the actual age by as much as 12%, which is thousands of years for Holocene thinning histories like those found in this thesis.